McVeigh [videorecording (DVD)] - Ott, Mike; Gioulakis, Alex; Allen, Alfie, 1986-; Gelman, Brett, 1976-; Benson, Ashley, 1989-; Carrigan, Anthony, 1983-; Letts, Tracy, 1965- (Decal, 2025)
After the Waco siege, a chilling plan brews in the mind of army veteran Timothy McVeigh. A haunting psychological thriller based on the harrowing real-life events of the deadliest act of domestic terrorism in American history.